Presence of the R1748X mutation in the NF1 gene in a Brazilian patient with ectropion uveae - Trovo-Marqui, A. B.; Goloni-Bertollo, E. M.; Teixeira, M. F.; Tajara, E. H. (Karger, 2004)
Congenital ectropion uveae is a rare, nonprogressive anomaly characterized by the presence of iris pigment epithelium on the anterior surface of the iris stroma and is occasionally associated with Rieger's anomaly, Prader-Willi syndrome and neurofibromatosis type 1 (NF1). The most important complication of ectropion uveae is congenital or juvenile glaucoma. We described a patient with ectropion and the mutation R1748X in the NF1 gene. This is the third report in the literature describing ectropion associated with neurofibromatosis. If this association is confirmed by other authors, the NF1 patients should be examined for the presence of ectropion and, consequently, for the development of glaucoma. Copyright (C) 2004 S. Karger AG, Basel.
Keywords: ectropion uveae; neurofibromatosis type 1; mutation